Persepsi Penyakit dan Kualitas Hidup di Kalangan Wanita dengan Kanker Payudara: Analisis Multivariat dari Indonesia - Inggriane Puspita Dewi; Shella Febrita Putri Utomo; Nordianna Seman; Zaina Farzana Permadi (Universitas Faletehan, 2025)
Breast cancer profoundly affects patients’ quality of life (QoL), yet the relative impact of illness perception compared to demographic factors remains underexplored. This study sought to identify key determinants of QoL using a comprehensive multivariate approach, aiming to examine how illness perception influences the QoL of patients with breast cancer in Indonesia. A cross-sectional study was conducted, involving 167 patients with breast cancer from the hospital's cancer unit who were selected by purposive sampling. Demographic data, illness perception, and QoL were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Measurement models assessed reliability (Cronbach's α, CR) and validity (AVE), while structural models evaluated path coefficients (β) and predictive power (R²) using SmartPLS 4.0. Research results showed illness perception emerged as a strong predictor of QoL (β = -0.558, p < 0.001; R² = 0.360), with emotional response (loading = 0.796) and perceived consequences (loading = 0.727) identified as key dimensions. Demographic variables showed negligible influence (R² = 0.0003). Reliability was acceptable for illness perception (α = 0.699, CR = 0.794) but poor for demographic factors (α = 0.248). Model fit indices suggested moderate adequacy (SRMR = 0.104, NFI = 0.515). Illness perception, especially emotional response and perceived consequences, strongly determines QoL. Psychological interventions, education, and emotional support should be prioritized over demographic factors in breast cancer care.